Westonci.ca offers fast, accurate answers to your questions. Join our community and get the insights you need now. Our platform provides a seamless experience for finding precise answers from a network of experienced professionals. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
Answer:
x y
-4 11
-2 7
0 3
2 -1
Step-by-step explanation:
plug in x to solve for y.
when x = -4:
y = -2(-4)+3 = 8 + 3 = 11
y = 11
when x = -2:
y = -2(-2)+3 = 4 + 3 = 7
y = 7
when x = 0:
y = -2(0) + 3 = 0 + 3 = 3
y = 3
when x = 2:
y = -2(2) + 3 = -4 + 3 = -1
y = -1
Step-by-step explanation & ANSWER BELOW IS IN BOLD:
Given the value of x, we can substitute the function rule.
Let's solve these problems together.
Note : Negative * Negative = Positive
If x= -4, then y = 11 because [tex]y=-2*-4 + 3 = 8+3=11[/tex]
If x = -2, then y = 7 because [tex]y=-2*-2+3=4+3=7[/tex]
If x = 0, then y = 3 because [tex]y=-2*0+3=0+3=3[/tex]
If x = 2, then y = -1 because [tex]y=-2*2+3=-4+3=-1[/tex]
Hope this helps :)
Have an awesome day!
We hope this was helpful. Please come back whenever you need more information or answers to your queries. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.